Self impression : life-writing, autobiografiction, and the forms of modern literature - Saunders, Max. (Oxford : Oxford University Press, 2010)
Max Saunders explores the ways in which modern writers from the 1870s to the 1930s experimented with forms of life-writing such as biography, autobiography, memoir, diary and journal for the purposes of fiction. He identifies a wave of new hybrid forms from the late 19th century and provides a fresh look at turn-of-the-century literature.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Biography as a literary form; Autobiographical fiction -- History and criticism; Literature -- 19th century -- History and criticism; Literature -- 20th century -- History and criticism